Peningkatan Pendapatan Bunga Bersih Dari Pengaruh Aktiva Produktif Pada Bank Central Asia Tahun 2017-2021 - Srisulistiowati , Dwi Budi; Suryani, Rani; Rejeki, Sri (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2021)
From the several sources of budget that the bank has collected, it is appropriate for the bank to prepare a budget placement program based on the distribution program by taking into account the policies that have been determined. The total budget collected by the bank consists of two types, namely the budget that cannot be loaned and the budget that can be lent. The existence of a budget that cannot be loaned will increase the cost of the budget that will be purchased by residents called the cost of funds, in the end it will force banks to be able to manage a budget that has been activated into a very useful source of income and can co-exist with other banks. To simplify the analysis, all the variables to be analyzed are combined and then calculated in the SPSS application, so that the results obtained are that the distributed credit variables are the most significantly correlated with interest income. The definition is that the higher the budget that is distributed to distributed credit, so that interest income tends to increase.